Can the Congenital Zika Virus Syndrome Crisis Contribute to Challenging Contemporary Discourses Against Abortion Legalization in Brazil? - Tamara Amoroso Gonçalves; Daniela Rosendo (Ethic@: an International Journal for Moral Philosophy)
In this paper we will explore the widespread of congenital Zika virus syndrome in Brazil associated with abyssal social inequalities as a trigger to push for abortion legalization, from a human rights perspective. Brazil has a very restrictive regulation on abortion, which allows the procedure only when the life of the mother is in danger, in cases of sexual violence and when the fetus suffers from anencephaly. Due to the growing influence of ultra-conservative forces in the Parliament the legislative debate on abortion has been blocked for many years in Brazil, making social movements seek the courts for advancements in this area. In this paper, we will present general data on the Zika epidemic, social inequalities and unequal access to health services as a background for the discussion on advancing abortion legalization in the country through judicial procedures, from a human rights perspective.